(untitled) (INMR - Innovation & Management Review, 2009)
This empirical study presents a teacher education project for the use of technology in the teaching-learning environment of a Business School in a higher education institution (HEI) in Rio de Janeiro, in order to spread e-learning as an innovation within the organization. First, the history of distance education in that institution is presented, from its initial implementation to the present time, as well as the motivation for the project. Within the scope of the project, the aim is to prepare teachers for e-learning and to identify individuals that could play the role of Champions in the process (ROGERS, 1995), i.e. e-learning multipliers in the organization. At this stage of the project (1st phase), the position of lecturers as to beliefs about the use of technology in the teaching process was mapped. Data were generated by means of discussions in forums and were submitted to content analysis. It was clear that lecturers who participated in the program identified the need for innovation in the education environment, with the appropriate infrastructure. They also recognize the importance of institutional support. Finally recommendations are made for innovation diffusion programs in HEIs.